Stonewall strong : gay men's heroic fight for resilience, good health, and a strong community - Andriote, John-Manuel (Rowman & Littlefield, 2017)
Stonewall Strong uses research, history, and firsthand accounts to examine gay men's remarkable resilience as it's been established and built over the years after the Stonewall riots. John-Manuel Andriote shows how the gay rights movements has contributed to personal resilience and a platform that promotes community, understanding, and good health.